Is there a Return-Risk Link in Education? - Pedro Telhado Pereira; Pedro Silva Martins (Institute for the Study of Labor (IZA), 2001)
Risk averse investors have to be compensated in higher expected returns when facing investments with higher risk. Education is an important investment therefore we use the results for 16 countries to test the positive relationship between return to education and the risk involved in this investment. It seems that most of the countries fit the pattern well: higher risk – higher return.
Keywords: I21; C29; J24; 330; Returns to Education; risk; quantile regression; Bildungsinvestition; Investitionsrisiko; Bildungsertrag; Welt